The Impact of AI on the Future of Education in Indonesia - Fauziddin, Mohammad; Adha, Twinda Rizki; Arifiyanti, Nurul; Indriyani, Fenny; Rizki, Lussy Midani; Wulandary, Verra; Reddy, Vankelu Sai Venkateswarlu (Educative: Jurnal Ilmiah Pendidikan, 2025)
Artificial Intelligence (AI) has the potential to revolutionize education in Indonesia by improving its quality and accessibility. The current study employed a Systematics Literature Review (SLR) method to analyze the impact of AI implementation in education. The findings revealed that AI can support adaptive learning, provide accurate assessments, and personalize the students' learning experiences. However, limited infrastructure, data privacy concerns, and the digital divide remain significant challenges. Effective utilization of AI requires teacher training and clear ethical policies to protect student privacy. By integrating AI technology, the education system of Indonesia can foster a more innovative and responsive learning environment, equipping students to face the challenges of the digital era. The current study also recommended that collaboration among the government, educational institutions, and private sectors is needed to maximize the potential of AI in education.